PENGARUH STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Fairisati, Neny Tresna; Mulyati, Diana Juni; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2016)
The value of company in investor perception towords the company success lavel which is often related to the price of the stock. The high value of the company will make the market believe is not only the present condition of the company but also the prospect of the company. Based on the previous studies, there are some factors influencing the value of the company, among them are : decision of funding, dividend policy, decision of stock, company growth and size of the company. Some of the factors have relationship and influence towards the inconsistent value of the company. The present study is aimed at finding out the influence of capital structute and company growth towards the value of company at manufacture companies of Indonesia Stock Exchange.            The population of the study was the manufacture industry registered at Indonesia Stock Exchange which was studied from 2014 up to 2015. The method used to determine samples was using purposive sampling method with some fixed criteria with the 1 samples of manufacture companies. The data used was the secondary data which was obtained from Indonesia Capital Market Directory from 2014 up to 2015.             The result of the study shows that: 1) capital structure has a positive influence toward the company value, 2) company growth has positive influence towards the value of the company.            Keywords: Capital Structure, Growth Of Company and Firm Value.